Política hidráulica y evolución de la estructura de la propiedad agraria: une ejemplo: las Cinco Villas de Aragón - Martínez Cordón, Ana María (Geographicalia, 2017)
The economic outcome of agricultural explotations is strongly influenciated by the structure of rural property. In this paper, results of an IRYDA action brought about in Zaragoza province, concerning rustic property are analyzed. It seems that a good profitability could be obtained through the use of suitable crops